International sourcing and asymmetry: how Western software entrepreneurs tap and decant Ukrainian engineering skills. (1st October 2012) - Graham Hollinshead; Jane Hardy
Abstract : The international IT industry has been hailed as the epitome of the new global economy, appearing footloose in its productive and marketing activities across national borders, and drawing on the talents of an apparently homogenous and internationally dispersed cadre of knowledge workers. In this paper we refer to recent international re-engineering of the software development process to suggest that it encompasses a division of labour amenable to spatial separation. By contextualising the delivery of architectural and creative functions in the Western part of Europe, and more routine activities in the post-socialist territory of Ukraine, we are able explore the embedded nature of dispersed inputs into product and service manufacturing in the sector, and the complex managerial issues associated with co-ordinating sourcing over highly diverse and asymmetrical institutional and cultural zones. We identifycontrasting strategies employed by IT companies to mitigate the risks associated with operating over distance and to capitalise on the reserves of engineering knowledge and skills possessed by 'nearshore' service providers.